The Gut in the Brain: the Effects of Bariatric Surgery on Alcohol Consumption - Blackburn, Ashley N. (Addict Biol, 2016)
Obesity represents a major medical and public health problem worldwide. Efforts have been made to develop novel treatments, and among them bariatric surgery is used as an effective treatment to achieve significant, long-term weight loss and alleviate medical problems related to obesity. Alcohol use disorder (AUD) is also a leading cause of morbidity and mortality worldwide. Recent clinical studies have revealed a concern for bariatric surgery patients developing an increased risk for alcohol consumption, raising concerns about development of AUD. A better understanding of the relationship between bariatric surgery and potential later development of AUD is important, given the critical need of identifying patients at high risk for AUD. This paper reviews current clinical and basic science research and discusses potential underlying mechanisms. Special emphasis in this review is given to recent work suggesting that, alterations in alcohol metabolism/pharmacokinetics resulting from bariatric surgery are unlikely to be the primary or at least the only explanation for increased alcohol use and development of AUD, as changes in brain reward processing are also likely to play an important role. Additional studies are needed to clarify the potential role and mechanisms of how bariatric surgery may increase alcohol use and lead to AUD development.